Social Media Fatigue and the Effectiveness of Digital Activism: A Case Study of the “17+8 People's Demands” Movement in Indonesia - Balqis Sulistiyani; Yayuk Lestari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study examines the phenomenon of social media fatigue (SMF) within the context of digital activism, focusing on the “17+8 People's Demands” movement in Indonesia in 2025. Data were collected qualitatively through content analysis of online media monitoring Instagram, TikTok, Facebook, YouTube, and X from August 28 to September 21, 2025. Findings reveal that after an initial surge of participation and viral attention, there was a sharp decline in engagement and discussion, driven by information overload, opinion polarization, and disappointment with the slow response from authorities. A significant concern is that despite the demands remaining unfulfilled, conversations on social media quickly ceased and were no longer discussed. This study confirms that while social media is effective in raising awareness, it is not necessarily efficient in driving structural or policy change. The results contribute to the literature on social media fatigue and the de-amplification of social issues in the digital age, highlighting the need for sustained activism strategies that integrate online and offline approaches.